Mitral Valve-in-Valve Implant of a Balloon-Expandable Valve Guided by 3-Dimensional Printing - Mao, Yu; Liu, Yang; Ma, Yanyan; Jin, Ping; Li, Lanlan; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background Our goal was to explore the role of 3-dimensional (3D) printing in facilitating the outcome of a mitral valve-in-valve (V-in-V) implant of a balloon-expandable valve. Methods From November 2020 to April 2021, 6 patients with degenerated mitral valves were treated by a transcatheter mitral V-in-V implant of a balloon-expandable valve. 3D printed mitral valve pre- and post-procedure models were prepared to facilitate the process by making individualized plans and evaluating the outcomes. Results Each of the 6 patients was successfully implanted with a balloon-expandable valve. From post-procedural images and the 3D printed models, we could clearly observe the valve at the ideal position, with the proper shape and no regurgitation. 3D printed mitral valve models contributed to precise decisions, the avoidance of complications, and the valuation of outcomes. Conclusions 3D printing plays an important role in guiding the transcatheter mitral V-in-V implant of a balloon-expandable valve. Clinical Trial Registration ClinicalTrials.gov Protocol Registration System (NCT02917980).